2015
DOI: 10.1088/1367-2630/17/2/023063
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dynamics in a tiered non-Markovian environment

Abstract: We introduce a new analytical method for studying the open quantum systems problem of a discrete system weakly coupled to an environment of harmonic oscillators. Our approach is based on a phase space representation of the density matrix for a system coupled to a two-tiered environment. The dynamics of the system and its immediate environment are resolved in a non-Markovian way, and the environmental modes of the inner environment can themselves be damped by a wider 'universe'. Applying our approach to the can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 64 publications
(134 reference statements)
2
17
0
Order By: Relevance
“…Appendix C: Approximation of dephasing time Ref. 30 allows us obtain an analytical estimate of the 'spin' coherence time in the presence of one or more oscillator modes. This is more appropriate than solutions to the canonical spin-boson model, as the discrete oscillator environment is too small to assume short environmental correlations times.…”
Section: Longitudinal Phononsmentioning
confidence: 99%
“…Appendix C: Approximation of dephasing time Ref. 30 allows us obtain an analytical estimate of the 'spin' coherence time in the presence of one or more oscillator modes. This is more appropriate than solutions to the canonical spin-boson model, as the discrete oscillator environment is too small to assume short environmental correlations times.…”
Section: Longitudinal Phononsmentioning
confidence: 99%
“…We consider two different weak-coupling techniques: time convolutionless (TCL) master equations 4 and a second method based on the phase-space representation of the full density matrix 10 (P-mat). Interestingly, we show that both approaches give rise to exactly the same criterion, despite their rather different nature.…”
mentioning
confidence: 99%
“…In the ‘grey area’ where a second-order expansion is no longer strictly justified, we find that the quality of the different approaches differs. Some of us have previously found that the P-mat method outperformed the commonly used secular, second-order Born-Markov master equation 10 . For the examples studied here, we find that a TCL ME gives slightly better short time dynamics than P-mat, whilst the latter frequently performs better at longer times as the system approaches thermalisation.…”
mentioning
confidence: 99%
“…A new analytical method based on a phase space representation of the system density matrix has been also proposed to study the dynamics of a discrete system in a two-tiered non-Markovian environment [52].…”
Section: Introductionmentioning
confidence: 99%